Design, synthesis and evaluation of a novel series of inhibitors reversing P‐glycoprotein‐mediated multidrug resistance. (14th June 2018) - Ghaleb, Hesham; Li, Huilan; Kairuki, Mutta; Qiu, Qianqian; Bi, Xinzhou; Liu, Chunxia; Liao, Chen; Li, Jieming; Hezam, Kamal; Huang, Wenlong; Qian, Hai
Abstract : Multidrug resistance (MDR) is still the main barrier to attaining effective results with chemotherapy. Discovery of new chemo‐reversal agents is needed to overcome MDR. Our study focused on a better way to obtain novel drugs with triazole rings that have an MDR reversal ability through click chemistry. Among 20 developed compounds, compound19 had a minimal cytotoxic effect compared to tariquidar and verapamil (VRP) and showed a higher reversal activity than VRP through increased accumulation in K562/A02 cells. Compound19 also played an important role in the P‐gp efflux function of intracellular Rh123 and doxorubicin (DOX) accumulation in K562/A02 cells. Moreover, compound19 exhibited a long lifetime of approximately 24 hr. These results indicated that compound19 is a potential lead compound for the design of new drugs to overcome cancer MDR. Abstract : Twenty triazol‐phenethyl‐tetrahydroisoquinoline‐based compounds have been synthesized. Among them, compound19 revealed a higher reversal activity than VRP by increasing the anticancer drugs accumulation in K562/A02 cells and persisted much longer chemo‐sensitizing effect (>24 hr) than VRP (>6 hr).